PELATIHAN CABANG OLAHRAGA BELADIRI KARATE PRAYA TENGAH - Herlina, Herlina; Burhan, Zakir; Ashari, Lalu Hasan; Nulhadi, Agus (LPPM Institut Pendidikan Nusantara Global, 2023)
Karate is a martial art that was developed in China in 1990. Karate is a self-defense technique with bare hands or without weapons.